NANOTECHNOLOGY FIGHTS CANCER AND GIVES NEW HOPES FOR LIFE: Life Science-Biotechnology - DR.M. JAHAN ARA (International Journal of Life Science and Pharma Research, 2013)
Nanotechnology has been a boon in medical field by delivering drugs to specific cells using nanoparticles. The new Nanotechnology techniques may have interesting applications for detecting cancer and may aid in giving patients more personalizing treatment protocols. Cancerous cells must travel long distances through the body to infect other organs. These metastasis’ cells should become more flexible, will be able to over come all sort of physical obstacles in the blood stream and within tiny and complex cell matrices of cell tissue. The new technology can detect at the nano level and this softness or flexibility of the cancerous cells